Boosting soil literacy in schools can help improve understanding of soil/human health linkages in Generation Z - Johnson, Karen L.; Stone, Wendy; Dominelli, Lena; Chivasa, Stephen; Clarke, Catherine E.; Gwandu, Tariro; Appleby, Joanne (Frontiers in Environmental Science, 2023)
Soil health underpins ecosystem services like food security and therefore underpins human health. Poor soil health is a global problem which is hindering attempts to deliver the UN’s Sustainable Development Goals. We focus on goals 3 (human health), 13 (climate change) which are intimately linked to goal 15 (soil health). Soil health is arguably most fragile in regions such as sub-Saharan Africa (SSA) where aged soils are characterised by poor nutrient and water holding capacity, and are largely deficient in micronutrients such as Zinc. Poor soil health coupled with the largely cereal-based diets can mean that micronutrient malnutrition is high in the region. In SSA, where much of the population is too poor to purchase mineral supplements, poor soil health (SDG15) can therefore negatively impact on human health (SDG3). We surveyed 3661 school children aged 13-15 in three African countries, Ghana, South Africa and Zimbabwe, for their ‘Attitudes, Behaviours and Competencies’ of soil, which we termed ‘ABC’. The ‘ABC’ survey results showed significant soil illiteracy. The survey showed that although students were generally equipped with a good attitude to (overall 52% positive) and behaviour towards soil (overall 60% engagement), they had little competency as to how to improve soil health (overall 23% knowledge). For example, less than 35% of respondents across all countries know that soil is living. Less than 13% of students are aware of the important role of soil in climate change mitigation. We believe that these two knowledge gaps must be addressed for Generation Z to understand the important linkages between climate change, soil and human health. We propose a hands-on ‘ethics of care’ approach to engage society with soil, piggybacking on existing climate change educational resources by building terrariums with living soil can empower children to learn about soil, plant, human and planetary health. The future of food security depends on Generation Z having soil literacy. Our survey clearly shows that students who think farming is a good way to make money have significantly higher levels of overall soil literacy. We propose that the future of human health depends on soil literacy.